CONFIDENTIAL EYES ONLY FOR ADDRESSEE (Tufts Archival Research Center, 2007)
Marginalia; Draft of a Trade Press Briefing for Ellen Merlo reporting: the basic factors motivating anti-smoking legislation, future issues the tobacco industry will face, current action, and the social forecast for the 21st century. Mentions federal and state excise taxes, the 1993 Environmental Protection Agency (EPA) report on the effect of smoking on non-smokers, and smoking bans in various states.